Spazio — pensiero — lingua. La concettualizzazione della città in italiano - Paliczuk, Aleksandra (Neophilologica, 2014)
The surrounding space has always interested people and provoked their curiosity. Reflections upon the concept of space are present in almost every philosophical school and approach, and also in other disciplines such as e.g. anthropology, sociology or linguistics. For some researchers space is a social product or historical product, for others — a product of human activities. The same way as space, the city has always intrigued and fascinated as a positive reference structure, a place in which one wants to live, dwell and work. This paper is an attempt at a cognitive analysis of the concept of città (city) in Italian. It endeavors to explain how Italians conceive and perceive città (city) by trying to show one of the ways of organizing its category. It comments on relations among thought, word and physical reality (meaning space) on the basis of the general notions of cognitive linguistics, e.g. categorization and conceptualization with reference to some of the main theories on the matter.